2003
DOI: 10.1023/a:1025794830705
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The glycosaminoglycan microenvironment of testicular hyaluronidase was simulated by multipoint covalent attachment of the enzyme to glycans as a result of benzoquinone activation. The efficiency of their binding was assessed using gel chromatography, ultrafiltration, titration of surface amino groups of the enzyme, electrophoresis, as well as judging by the value of residual endoglycosidase activity and its inhibition with heparin. Copolymer glycosaminoglycans, such as dermatan sulfate and heparin, inactivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…It has been reported that GAGs having iduronic acid residues in their disaccharide units such as heparin or DS (Fig. 1B) can be a potent inhibitor of HAases from testis and snake venom [19,20]. Therefore, we concluded that HA samples that were not digested with testicular HAase were due to the presence of contaminated DS, although we did not perform any studies using an antibody specific to DS.…”
Section: Cellulose Acetate Membrane Electrophoresismentioning
confidence: 85%
“…It has been reported that GAGs having iduronic acid residues in their disaccharide units such as heparin or DS (Fig. 1B) can be a potent inhibitor of HAases from testis and snake venom [19,20]. Therefore, we concluded that HA samples that were not digested with testicular HAase were due to the presence of contaminated DS, although we did not perform any studies using an antibody specific to DS.…”
Section: Cellulose Acetate Membrane Electrophoresismentioning
confidence: 85%
“…16,17 In the present work, dextran was functionalized at its reducing end-group D-glucose residue with a reactive carboxylate group by treatment with a molar excess of e-aminocaproic acid in the presence of sodium cyanoborohydride. The activated dextran was further attached to the free amino groups located at the protein surface of catalase by using a water-soluble carbodiimide as coupling agent.…”
Section: Resultsmentioning
confidence: 99%
“…The first approach was realized by stabilization of proteins against glycation by creation of polysaccharide envi ronment around them. This was achieved by multiple covalent attachment of such glycosaminoglycan as chondroitin sulfate (CS) to a known carbohydrase hyaluronidase (HU) [9]. Resultant HU CS derivatives exhibited higher stability than native HU during glyca * To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronidase chondroitin sulfate conjugate (HU CS) was prepared as described earlier [9]. Remaining endoglycosidase activity of HU CS repre sented 76⎯78% of initial enzyme activity and the modification degree of amino groups was 84⎯86%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation